PACT A Partnership to Fight Cancer in Developing Countries - -, J.P. Cayol (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45503308/PACT-A-Partnership-to-Fight-Cancer-in-Developing-Countries